2020
DOI: 10.3390/app10165517
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study on the Performance of Asphalt Mixes Modified with a Novel Composite of Diatomite Powder and Lignin Fiber

Abstract: The performance and the fundamental weaknesses of asphalt mix under environmental temperature and water effects have made researchers try to modify the asphalt mix properties by using the proper additives. For this reason, this paper aims to improve the anti-cracking performance and water stability of asphalt pavement by adding a novel composite of diatomite and lignin fiber in asphalt mixes. Four types of asphalt mixes, including control asphalt mix (CAM), diatomite modified asphalt mix (DMAM), lignin fiber m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Tang et al [ 34 ] explored the effect of alkali-treated waste betel nut fiber (BNF) on the water stability of asphalt mixture; the results showed that for the AC-13 gradation, the optimal combination of multi-response variables was a fiber content of 0.2561%, fiber shear time of 12.78 min, and asphalt-aggregate rate of 5.82%. Abdelsalam et al [ 35 ] carried out a laboratory study on the properties of asphalt mixture modified with a new composite composed of diatomaceous earth powder and lignin fibers. Results revealed that the use of the composite in asphalt mixture led to an enhancement in the asphalt pavement performance.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al [ 34 ] explored the effect of alkali-treated waste betel nut fiber (BNF) on the water stability of asphalt mixture; the results showed that for the AC-13 gradation, the optimal combination of multi-response variables was a fiber content of 0.2561%, fiber shear time of 12.78 min, and asphalt-aggregate rate of 5.82%. Abdelsalam et al [ 35 ] carried out a laboratory study on the properties of asphalt mixture modified with a new composite composed of diatomaceous earth powder and lignin fibers. Results revealed that the use of the composite in asphalt mixture led to an enhancement in the asphalt pavement performance.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high strength and green environmental protection of BF, the related research on BF-modified asphalt has entered people's field of vision [15,16]. When the BF content is 2% and the length is 9 mm, BF-modified asphalt enhances the stress dissipation capacity at low temperatures to a certain extent, showing excellent rheological properties, and the BF is spatially distributed in the asphalt mortar, which has better stability and enhancement [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…), the remaining polymer carbohydrates can also be used to create bio-asphalt. Some researchers use soil as a modifier, such as nano clay [ 14 ], diatomite [ 15 , 16 ], organically modified bentonite [ 17 , 18 ] and so on. Take bentonite as an example.…”
Section: Introductionmentioning
confidence: 99%